2005
DOI: 10.1182/blood-2004-06-2297
|View full text |Cite
|
Sign up to set email alerts
|

MALT1 and the API2-MALT1 fusion act between CD40 and IKK and confer NF-κB-dependent proliferative advantage and resistance against FAS-induced cell death in B cells

Abstract: The most frequently recurring translocations in mucosa-associated lymphoid tissue (MALT) B-cell non-Hodgkin lymphoma, t(11;18)(q21;q21) and t(14;18)(q32; q21), lead to formation of an API2-MALT1 fusion or IgH-mediated MALT1 overexpression. Various approaches have implicated these proteins in nuclear factor B (NF- B IntroductionFour recurrent chromosomal translocations have been described in non-Hodgkin B-cell lymphoma of the mucosa-associated lymphoid tissue (MALT) type. Two of them, t(14;18)(q32;q21) and t(11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2005
2005
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 61 publications
1
54
0
1
Order By: Relevance
“…Thus, it is imperative that we gain an understanding of the precise molecular mechanisms by which API2-MALT1 functions to promote lymphomagenesis. Several recent studies have shown that expression of API2-MALT1 protects cells from apoptosis and promotes proliferation and that NF-kB activation is required for these effects (Hosokawa et al, 2004;Stoffel et al, 2004;Ho et al, 2005). Our studies demonstrate for the first time that the API2 moiety mediates oligomerization of API2-MALT1 via heterotypic interaction of the BIR1 domain with the MALT1 moiety.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Thus, it is imperative that we gain an understanding of the precise molecular mechanisms by which API2-MALT1 functions to promote lymphomagenesis. Several recent studies have shown that expression of API2-MALT1 protects cells from apoptosis and promotes proliferation and that NF-kB activation is required for these effects (Hosokawa et al, 2004;Stoffel et al, 2004;Ho et al, 2005). Our studies demonstrate for the first time that the API2 moiety mediates oligomerization of API2-MALT1 via heterotypic interaction of the BIR1 domain with the MALT1 moiety.…”
Section: Discussionsupporting
confidence: 58%
“…This suggests that API2-MALT1 may represent a gain-offunction mutant that promotes lymphomagenesis through inappropriate NF-kB activation. In support of this notion, recent studies show that expression of API2-MALT1 protects cells from apoptosis and promotes proliferation and that NF-kB activation is required for these effects (Hosokawa et al, 2004;Stoffel et al, 2004;Ho et al, 2005). In this report, we explore the mechanism by which the API2 moiety contributes to API2-MALT1-dependent stimulation of NF-kB.…”
Section: Introductionmentioning
confidence: 69%
“…87 It has been proposed that chronic antigenic stimulation by H. pylori triggers T-cell-mediated B-cell growth via activation of CD40 and NF-kB pathway early in the development of gastric MALT lymphoma. In this connection, Ho et al 88 recently examined the effect of stably expressed MALT1 and API2-MALT1 in human B-cell lines on the NF-kB signaling pathway and elegantly demonstrated that cytoprotection mediated by NF-kB, once activated in a CD40-mediated immune response, is maintained and enhanced through deregulation of MALT1 or formation of API2-MALT1 fusion.…”
Section: Molecular Pathogenesis Of Malt Lymphoma M Nakagawa Et Almentioning
confidence: 99%
“…111 Two recent studies also reported that API2-MALT1 confers resistance to UV-induced and p53-dependent apoptosis. 88,112 Stoffel et al demonstrated that antiapoptotic effect of API2-MALT1 depends on its activity of NF-kB activation.…”
Section: Two Signaling Pathways Underlying the Antiapoptotic Effect Bmentioning
confidence: 99%
“…In mature B cells, signaling through CD40 promotes survival, somatic hyper-mutation and class-switch recombination, and the defective CD40 signaling results in hyper-IgM syndrome [31,32]. Interestingly, signaling through CD40 activates NF-jB and constitutive signaling through CD40 has been shown to promote survival of B cell lineage nonHodgkin's lymphoma [33,34]. IKK activation upon CD40 receptor ligation is mediated by TNF receptorassociated factors (TRAF) 1, 2, 5 and 6 and appear to be independent of the signaling components that connect BCR to IKK [35,36].…”
mentioning
confidence: 99%